Manajemen Humas Dalam Penerapan Pembelajaran Daring Selama Pandemi Covid-19 di SD Al-Bayyinah Makassar - Nur Adelia Yulianti AP; Ansar Ansar (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
This research aims to determine Management Public Relations in the Implementation of Online Learning During the COVID-19 Pandemic at SD Islam Al Bayyinah Makassar. Public relations management in this case is seen from planning, organizing, implementing, controlling and evaluating of public relations. The approach used is a qualitative with descriptive type of research. Data analysis in this study used the Miles and Huberman model. Checking the validity of the data using triangulation techniques. The results showed that public relations planning was carried out to determine public relations goals and strategies in carrying out online public relations based on the needs of the school public. In this case, the organizing stage is also carried out, where it is decided that homeroom teachers, subject teachers with the assistance of school administration staff are in charge of carrying out previously planned public relations activities, which include presentations of school activities carried out at the beginning of the semester, creating whatsapp groups for each class, monthly online meetings and the COVID-19 vaccination program in collaboration with Puskesmas Pampang. The media used in the implementation of public relations are cellphones and laptops, using online applications including zoom, school web, youtube, facebook, instagram and whatsapp. Control in the implementation of public relations is carried out by the head of SD Islam Al Bayyinah Makassar who directly monitors public relations activities and communicates online to the coordinator and homeroom teacher. evaluation of public relations activities is carried out online with the foundation, principal, teachers, and parents/guardians of students by presenting detailed information about online learning conducted by the school in one semester.